Therapeutic Role of Yoga and Pathophysiological Insights of Pelvic Floor Dysfunction in Polycystic Ovary Syndrome (PCOS) - Mishra, Shringarika; Khattar, Gautam; Sehrawat, Meenakshi; Pandey, Aayush; Singh, Pawan Kumar; Tripathi, Deepti; Tiwari, Mahim (Journal of Neonatal Surgery, 2025)
Polycystic Ovary Syndrome (PCOS) is a prevalent hormonal condition impacting around 8-13% of women of reproductive age, with up to 70% of cases remaining undiagnosed. One of the many symptoms of PCOS is pelvic floor dysfunction, which commonly includes urinary incontinence, pelvic pain, and sexual dysfunction, affecting many women with the condition. While hormonal and metabolic dysregulation are central to PCOS pathophysiology, emerging evidence suggests that Yoga therapy may play a beneficial role in improving pelvic muscle function. This review aims to explore the underlying mechanisms through which Yoga therapy may modulate pelvic floor function in PCOS patients. Through a review of relevant literature, We investigate the impact of Yoga on the strength of pelvic floor muscles, flexibility, autonomic nervous system balance, and hormonal regulation, with a focus on how these factors intersect in the context of PCOS